Notes on taxonomic identity and typification of Fagraea coromandelina (Gentianaceae) - Venugopal, Divya K.; Francis, Dani; Mohan, Vishnu; Nampy, Santhosh (Phytotaxa, 2018)
The genus Fagraea Thunberg (1782: 132), belonging to the family Gentianaceae, is represented by 70 species in the world (Struwe et al. 2002). It is distributed in India, Sri Lanka, Sumatra, Malay Peninsula, Borneo, New Guinea, French Polynesia, China, Philippines and Australia. Clarke (1885) reported 5 species from the present political boundary of India, of which 2 species were recorded by Gamble (1921) from South India. The genus includes glabrous epiphytic trees or shrubs, with simple, opposite and coriaceous leaves, fragrant flowers and pulpy berries with a persistent calyx.